Effects of graphic organizers on aesthetic reading experience - Mendhakar, Akshay; Płużyczka, Monika; Leder, Helmut (Frontiers in Language Sciences, 2025)
The aesthetics of reading have received relatively little research attention, particularly in the context of foreign language readers. In this study, we investigate the impact of text mining-powered graphic organizers (GOs) on aesthetic reading experience with English as a foreign language (EFL) readers. Shusterman's framework of aesthetics was applied to measure reading comprehension, experience, and literary beauty perception. A between-group experiment design (N = 52) was conducted, where Norwegian students enrolled in the International Baccalaureate classes of Lillestrøm High School were recruited. Participants in the experimental condition interacted with GOs before reading the first three chapters of English versions of Pride & Prejudice, while those in the control condition solely read the same texts without interacting with GOs. A statistically significant enhancement in comprehension scores across all subdomains —summarization, vocabulary, and overall comprehension—was associated with the use of GOs. However, the introduction of GOs did not improve or hinder the reading experience or the perceived literary beauty of the text. These findings highlight the efficacy of automatically extracted GOs in improving specific aspects of the aesthetic reading experience. The implications of such findings for individual domains of reading aesthetics and foreign language readers are discussed.